Adoption of Agricultural Marketing Technologies by Farmers of Northern Bangladesh: A Binary Logistic Analysis to Determine the Factors Influencing Farmers’ Decision - Haque, Md. Ziaul (Asian Business Review, 2019)
Low adoption of agricultural marketing technologies in the field of agricultural commodities marketing is one of the main reasons for profit loss of the farmers in Bangladesh. This paper examines the factors that influence farmers’ decision of modern agricultural marketing technologies adoption in Northern Bangladesh. By using questionnaire survey the researcher collect data from 216 farmers in Dinajpur and Naogaon district in Northern Bangladesh and the binary logistic regression model was estimated to find out the factors influence farmers decision. Seven independent variables i.e. age of the farmer, formal education of the farmer, farm size, level of expected benefits, off-farm income generating activities, access to institutional credit and training about use of marketing technologies are statistically significant factors that influence the decision of farmers to adopt modern agricultural marketing technologies in Northern Bangladesh. So it is concluded that the farmers’ decision to adopt modern agricultural marketing technologies depends on their socio-economic status and organizational effectiveness. We recommend that such policies should be made so that the positive impact factors on technologies adoption are properly utilized and negative issues are reduced.